Diastolic function and cardiovascular risk among patients with severe obesity referred to a lifestyle-program - a pilot study - Oldervoll, Line M.; Gjestad, Rolf; Hilmarsen C, Christina; Ose, Anders; Gullikstad, Lisbeth; Wisløff, Ulrik; Kulseng, Baard; Grimsmo, Jostein (Scandinavian cardiovascular journal : SCJ, 2023)
Objectives. Severe obesity is associated with a high risk of comorbidities and alterations of cardiac structure and function. The primary aim of the study was to investigate the proportion of diastolic dysfunction (DD) at baseline, and changes in cardiac function from baseline (T1) to 6 months follow-up (T2) among participants with severe obesity attending a lifestyle-intervention. The secondary aim was to explore changes in body mass index (BMI), physical fitness (VO 2peak ) and cardiovascular risk from T1 to T2 and 12 months follow-up (T3). Design. This was an open single-site prospective observational study. Patients were recruited from an obesity clinic to a lifestyle-intervention consisting of three 3-weeks intermittent stays over 12-months period. Echocardiography was performed at T1 and T2 and BMI, VO 2peak and cardiovascular risk measured at T1, T2 and T3. Results. Fifty-six patients were included (mean age 45.1 years; BMI 41.9). Six of 52 patients (12%) had grade 1 DD at T1, while five subjects had DD at T2. E/A ratio (11%, p = .005) and mitral deceleration time (9%, p = .014) were improved at T2. A reduction in BMI (-1.8, p < .001) and improvement in VO 2peak (1.6 mL/kg min, p = .026) were assessed at T2 and this improvement persisted at T3. The total cardiovascular risk score was not significantly changed. Conclusion. The patients with severe obesity had low prevalence of DD. For all participants, an improvement in diastolic parameters, and an important initial weight loss was observed. Clinical Trial number: NCT02826122